Immune response patterns in non‐communicable inflammatory skin diseases. (15th January 2018) - Eyerich, K.; Eyerich, S.
Abstract: Non‐communicable inflammatory skin diseases (ncISD) such as psoriasis or atopic eczema are a major cause of global disease burden. Due to their impact and complexity, ncISD represent a major challenge of modern medicine. Dermatology textbooks describe more than 100 different ncISD based on clinical phenotype and histological architecture. In the last decades, this historical description was complemented by increasing molecular knowledge – and this knowledge is now being translated into specific therapeutics. Combining the enormous advances made in lymphocyte immunology and molecular genetics with clinical and histological phenotyping reveals six immune response patterns of the skin – type I immune cells cause the lichenoid pattern characterized by immune‐mediated cell death of keratinocytes; type II immune cells underlie the eczematous pattern with impaired epidermal barrier, infection and eosinophils as well as the bullous pattern with loss of epithelial integrity; Th17 cells and ILC3 mediate the psoriatic pattern characterized by acanthosis, high metabolic activity and neutrophils; dysbalance of regulatory T cells causes either the fibrogenic pattern with rarefication of cells and dermal thickening or the granulomatous pattern defined by formation of granulomas. With more and more specific therapeutic agents approved, classifying ncISD also according to their immune response pattern will become highly relevant. This review defines the six immune response patterns of ncISD and highlights therapeutic strategies targeting key lymphocyte mediators.